OVERVIEW OF THE PERCENTAGE OF ACCURACY IN CODING PNEUMONIA DIAGNOSES BASED ON ICD-10 ACCORDING TO PNPK 2023 AT THE UDAYANA TYPE II HOSPITAL IN DENPASAR CITY - Sang Gede Ary Yoga Pratama; Nurul Faidah; I Gusti Agung Ngurah Putra Pradnyantara (PT. Jurnal Center Indonesia Publisher, 2025)
The accuracy of disease diagnosis coding is an important indicator in the management of medical records and health service claims. This study aims to determine the percentage of accuracy in coding pneumonia diagnoses based on ICD-10 according to the 2023 National Medical Practice Guidelines (PNPK) at Udayana Hospital II in Denpasar. The research method used was quantitative descriptive with a total sampling approach of 72 medical records of pneumonia patients during the period from October 1, 2024, to December 31, 2024. The research instrument was a checklist for assessing the accuracy of diagnosis codes based on the provisions of ICD-10 and PNPK Pneumonia 2023. The results showed that 51 files (70.8%) were coded accurately, while 21 files (29.2%) were coded inaccurately. The inaccuracy in coding was due to a lack of supporting tests, such as microbiological tests, as well as the excessive workload of the coders. These findings indicate the need for an analysis of coders' workload to measure the effectiveness and efficiency of their tasks, time management, and priorities. This study is expected to serve as evaluation material to improve the quality of service and efficiency of hospital administration.